2013
DOI: 10.1109/jmems.2013.2262595
|View full text |Cite
|
Sign up to set email alerts
|

PDMS Selective Bonding for the Fabrication of Biocompatible All Polymer NC Microvalves

Abstract: Microvalves are commonly used in microfluidic systems to control precisely the liquid flow. In this paper, the design and fabrication of a normally-closed (NC) all-polymer membrane-type microvalve is described. The microvalve with a diameter and thickness of 5mm and 3 mm, respectively, is fabricated completely in biocompatible polydimethylsiloxane (PDMS). The opening pressure, which depends on the adhesion between the membrane and the slab, is reduced to the noticeably low value of 3.4 kPa by the surface oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The energy density of the adhesion of PDMS to a well prepared (polished and cleaned) metal surfaces is w200500 kPa. [ 31,32 ] Given the microscopic surface roughness of the particles used in MAEs and, as a consequence, the inevitable imperfectness of the coating (experimental observations to that effect are reported in ref. [33]), we reduce the estimate to w100200 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…The energy density of the adhesion of PDMS to a well prepared (polished and cleaned) metal surfaces is w200500 kPa. [ 31,32 ] Given the microscopic surface roughness of the particles used in MAEs and, as a consequence, the inevitable imperfectness of the coating (experimental observations to that effect are reported in ref. [33]), we reduce the estimate to w100200 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…By pouring the PDMS mixture into the master mold, followed by degassing in a vacuum chamber, and curing, the channel structures are fabricated. The pattern is then peeled from the master mold and sealed to a substrate, typically glass or PDMS, by various methods, such as plasma treatment (Brian and Ellis 2016;Friend and Yeo 2010;Jahanshahi et al 2013;Li et al 2013;Nan et al 2015;Shiu et al 2008;Tan et al 2010;Wong and Ho 2009;Yaozhong et al 2014). Other bonding methods are discussed in Karadimitriou et al (2013).…”
Section: Silicon- Glass-and Polymer-based Microfluidicsmentioning
confidence: 99%
“…The results reported in this paper permit the design of a polymeric valve showing specific performances in terms of OP. The valve profile has been described by univocally defining the correspondent parameters (these details, in many articles, are partial, omitted, or described in a non parametric manner) [9,10,16,18,19]. Another important novelty compared to the state-of-the-art is the accurate parameter analysis, conducted with the aim of highlighting which parameters were more significant for valve performance.…”
Section: Fabrication and Validationmentioning
confidence: 99%
“…Mohan et al reported interesting considerations concerning the design and the application of elastomeric microvalves, focusing on actuation pressure minimization, reliable operation and convenient integration into complex microfluidic devices [15]. Jahanshahi et al focused on the design of a micro-valve characterized by a high pressure range and a relatively high sealing capability (no flow up to 0.6 MPa reverse pressure) [16]. Hilbert and colleagues introduced an innovative micro-valve manufacturing technique by using PDMS loaded with neodymium particles, to adjust the switching point of each single valve [17].…”
Section: Introductionmentioning
confidence: 99%